2005
DOI: 10.1063/1.1899763
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from AlN nanorod array

Abstract: Single-crystalline mushroom-like AlN nanorod array has been synthesized. The AlN nanorods, with diameters of 50–200nm and lengths of several micrometers, are distributed uniformly with density of 107–108rods∕cm2. The field emission measurements show that the turn-on field is 8.8V∕μm at a field emission current density (J) of 10μA∕cm2, and the J (10.31mA∕cm2) fluctuation is as small as 2% within an hour. The relationship between the nanostructure and field emission properties is discussed. The low turn-on field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 25 publications
1
51
1
Order By: Relevance
“…The boiling point of NH 3 is -33°C. Because of the low sublimation temperature of AlCl 3 and the low boiling point of NH 3 , AlN has been observed to form even at 600°C or lower via the gas-phase reaction of AlCl 3 and NH 3 : [11,12] AlCl…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The boiling point of NH 3 is -33°C. Because of the low sublimation temperature of AlCl 3 and the low boiling point of NH 3 , AlN has been observed to form even at 600°C or lower via the gas-phase reaction of AlCl 3 and NH 3 : [11,12] AlCl…”
mentioning
confidence: 99%
“…For example, FE properties of various AlN nanostructures have been investigated. The turn-on fields of various 1D aluminum nitride nanostructures have been measured, such as nanowires (8.8 V lm -1 ), [3] nanocones (12 V lm -1 ), [5] nanotips (3.1-4.7 V lm -1 ), [6,7] and hierarchical comb-like structures (2.45-3.76 V lm -1 ). [8] On the other hand, reports on the luminescence properties of AlN nanostructures are scarce.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies on fabrication and characterization of AlN nanostructures have been reported. [1][2][3][4][5][6][7] Several promising applications such as field emitters, [8][9][10][11] hydrogen storage media, 12,13 light emitting devices, [14][15][16] and photo detectors 17 have been demonstrated. AlN nanorods also served as the barrier layer in GaN/AlN quantum dots/wire system for single photon source owing to the strong confinement of electron-hole pair as a result of its large band offset.…”
mentioning
confidence: 99%
“…It is well known that structures at the nanometer scale exhibit peculiar effects that make them interesting candidates for future quantum information technology [1], UV [2] and field emitters [3] or chemical [4] [5] and temperature sensors. The fabrication of quantum gates and qubit manipulation is an essential part for such technology.…”
Section: Introductionmentioning
confidence: 99%